INFLUÊNCIA DE ÉPOCAS DE SEMEADURA E CULTIVARES NA INCIDÊNCIA DO MOFO BRANCO NA CULTURA DA SOJA - Pierre, Marcelo Luiz Cunha (2015)
Soybean is a crop of great importance worldwide and Brazil is the second largest producer of it. Several factors affect the crop yield and the diseases is one of the most important, accounting annual losses estimated between 15 and 20%. The White mold, caused by the fungus Sclerotinia sclerotiorum, is one of the oldest diseases and currently, is considered one of the main soybean disease, which has been caused high losses in recent seasons and is difficult to control. Therefore many integrated management practices are recommended for the disease management. This study aimed to evaluate the influence of sowing time of soybean, with three soybean cultivars during two growing seasons. The experiments were conducted in Arapoti-PR, in a naturally infested area (55 sclerotia / m2) during the seasons 2011/2012 and 2012/2013. The design block randomized in a factorial arragement was used in the tests, consisting of three cultivars (NS 4823 RR, BMX Apollo RR and BMX Turbo RR in 2011/12 and NS 4823 RR, BMX Apollo RR and BMX Ativa RR in 2012/13) and seven sowing dates to each season, which began in September continuing for fortnightly intervals until the month of December. The disease incidence and severity and the crop yield (kg ha-1) were evaluated. For the analyzes of the results, the statistical program Assistat 7.7 ® and the Tukey test at 5% probability were used. In both seasons was no interaction between sowing dates and cultivars on the incidence of the disease. In the 2011/12 growing season, no disease was observed at the 1st, 2nd and 7th sowing times, being the 3rd sowind time the most favorable to the disease development, followed by the 4th sowing time. Regarding cultivars, there was no difference between cultivar BMX Apollo RR and BMX Turbo RR, but on the cultivar NS 4823 RR lower incidence level of disease was observed than the others. In the season 2012/13 the 4th sowing time was most favorable to the development of the disease, followed by the 3rd sowing. The 1st, 5th, 6th and 7th sowing times did not differ to each other, and among them only he fifth sowing time presented disease incidence. Among the cultivars, the BMX Ativa RR had the highest incidence level of the 2012/13 season, differing from the others. In the 2012/13 season, again, the cultivar NS 4823 RR achieved the lowest incidence and did not differ from BMX Apollo RR. The severity evolution of white mold was similar between the three cultivars, in both seasons. The rain during the flowering was essential for the development of the disease and the temperature, especially when above 30 ° C, was limiting for the occurrence of the disease in the two seasons. The cultivar NS 4823 RR had the lowest incidences in the two seasons, even under favorable weathers conditions, possibly due its maturity group and canopy (less branches), disadvantaging the favorable microclimate conditions for the diseae development.